2016
DOI: 10.1371/journal.pone.0166583
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Molecular Mechanisms of Paradoxical Activation in the BRAF Kinase Dimers: Atomistic Simulations of Conformational Dynamics and Modeling of Allosteric Communication Networks and Signaling Pathways

Abstract: The recent studies have revealed that most BRAF inhibitors can paradoxically induce kinase activation by promoting dimerization and enzyme transactivation. Despite rapidly growing number of structural and functional studies about the BRAF dimer complexes, the molecular basis of paradoxical activation phenomenon is poorly understood and remains largely hypothetical. In this work, we have explored the relationships between inhibitor binding, protein dynamics and allosteric signaling in the BRAF dimers using a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 149 publications
1
19
0
Order By: Relevance
“…This binding shifts the equilibrium toward Raf's open state, permitting dimerization and activation of the kinase domain. 35,[60][61][62] A similar membrane recruitment and equilibrium shift scenario was also suggested for tumor suppressor RASSF5, consistent with experimental observations. 63,64 In PI3K the autoinhibition is relieved by the RTK's phosphorylated motif.…”
Section: Discussionsupporting
confidence: 84%
“…This binding shifts the equilibrium toward Raf's open state, permitting dimerization and activation of the kinase domain. 35,[60][61][62] A similar membrane recruitment and equilibrium shift scenario was also suggested for tumor suppressor RASSF5, consistent with experimental observations. 63,64 In PI3K the autoinhibition is relieved by the RTK's phosphorylated motif.…”
Section: Discussionsupporting
confidence: 84%
“…As a small p21 guanosine triphosphatase (GTPase), Ras plays a central role in cellular signal transduction pathways (Lacal et al, 1986;Lu et al, 2016a;Malumbres and Barbacid, 2003), including proliferation, differentiation, apoptosis, and senescence (Quinlan and Settleman, 2009;van Hattum and Waldmann, 2014), by binding effectors and regulators, such as Raf and phosphatidylinositol 3-kinase (PI3K) (Yan et al, 1998). Raf leads to cancer via major signaling cascades, primarily the Raf/MEK/ERK (MAPK) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Raf activation requires active Ras that anchors to the plasma membrane (PM). Membrane-anchored, active Ras binds Raf, promoting homodimerization of Raf's catalytic kinase domain and trans-autophosphorylation (Jambrina et al, 2016;Tse and Verkhivker, 2016). Active Raf dimer phosphorylates and activates MEK1/2, which induces ERK1/2 activation, with the phosphorylation signal cascading downstream.…”
Section: Introductionmentioning
confidence: 99%
“…Computational analysis of residue interaction networks and community analysis have shown that local dynamic modules anchored around functional residues can serve as building blocks to connect distant functional regions and to mediate allosteric conformational transitions [94,252,[265][266][267][268]. Dynamic and coevolutionary residue correlations may also act as synchronizing forces that determine modular organization of allosteric interaction networks and enable efficient allosteric regulation [94,269,270]. These results have motivated the development of novel community-based methods for modelling ensembles of allosteric communication pathways in protein structures [94,269,270].…”
Section: Coevolution and Residue Interaction Networkmentioning
confidence: 99%
“…Dynamic and coevolutionary residue correlations may also act as synchronizing forces that determine modular organization of allosteric interaction networks and enable efficient allosteric regulation [94,269,270]. These results have motivated the development of novel community-based methods for modelling ensembles of allosteric communication pathways in protein structures [94,269,270]. Using this computational framework, it was found that efficient allosteric communications in various signalling proteins could be controlled by structurally stable functional centers that exploit dynamically coupled residues in their local communities to propagate cooperative structural changes.…”
Section: Coevolution and Residue Interaction Networkmentioning
confidence: 99%